2021
DOI: 10.2147/ijn.s289008
|View full text |Cite
|
Sign up to set email alerts
|

Nanotoxic Effects of Silver Nanoparticles on Normal HEK-293 Cells in Comparison to Cancerous HeLa Cell Line

Abstract: Purpose Biomimetic approaches for the synthesis of silver nanoparticles (AgNPs) had created a substantial impression among the research community that focuses on nano-bio interactions. In this study, an eco-friendly method using Rhizophora apiculata aqueous leaf extract as a reductant-rich hydrosol was followed to synthesize AgNPs and test its cytotoxicity. Methods To optimise the parameters for the synthesis of AgNPs, central composite design… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 59 publications
(30 citation statements)
references
References 74 publications
2
19
0
1
Order By: Relevance
“…Exposure to the two largest particle sizes, 80 and 100 nm, did not result in significant mortality (Figure 3). Overall, this is consistent with the literature, which shows that nanoparticle toxicity in zebrafish is size-dependent, with smaller nanoparticles being more toxic [29,34,35]. The toxicity observed in the studies with shielded AgNPs eliminates the contribution of Ag + to toxicity.…”
Section: Toxicity Testingsupporting
confidence: 91%
See 4 more Smart Citations
“…Exposure to the two largest particle sizes, 80 and 100 nm, did not result in significant mortality (Figure 3). Overall, this is consistent with the literature, which shows that nanoparticle toxicity in zebrafish is size-dependent, with smaller nanoparticles being more toxic [29,34,35]. The toxicity observed in the studies with shielded AgNPs eliminates the contribution of Ag + to toxicity.…”
Section: Toxicity Testingsupporting
confidence: 91%
“…Similarly, Liu et al (2019) noted that size is a bigger contributor to toxicity than surface coating [34]. However, the stability of coatings used in past research has been much less robust, with toxicity being attributed to changes in stability and aggregation over time [34]. In contrast, this study's coated particles were found to be stable, with negligible dissolution or aggregation beyond the timeframe of the zebrafish exposures.…”
Section: Toxicity Testingmentioning
confidence: 66%
See 3 more Smart Citations